2015
DOI: 10.3746/jkfn.2015.44.2.200
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Tenebrio molitor Larval Extracts against Hepatocellular Carcinoma

Abstract: Various natural products or their derivatives, mostly originating from plants, fungi, and bacteria, have been exploited as therapeutic drugs to treat various human diseases. In addition to previously explored organisms, research on natural compounds has now expanded into unexamined living organisms in order to identify novel bioactive substances. Here, we determined whether or not the larval form of the mealworm beetle Tenebrio molitor, a species of darkling beetle, contains cytotoxic substances that exclusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In terms of biological activity, recent studies have reported that T. molitor larvae may protect against hepatocellular carcinoma (Lee et al 2015), inhibit beta-secretase 1 enzyme activity related to accumulation of beta-amyloid (Youn et al 2014), and alleviate obesity in vitro and in vivo (Seo et al 2017). However, the antioxidant activity of T. molitor larvae has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of biological activity, recent studies have reported that T. molitor larvae may protect against hepatocellular carcinoma (Lee et al 2015), inhibit beta-secretase 1 enzyme activity related to accumulation of beta-amyloid (Youn et al 2014), and alleviate obesity in vitro and in vivo (Seo et al 2017). However, the antioxidant activity of T. molitor larvae has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most popular edible insect species worldwide is mealworm larva (MWL) (Tenebrio molitor) belonging to order Coleoptera and family Tenebrionidae. MWL extract showed cytotoxic activity against prostate cancer (PC-3 and 22Rv1), cervical carcinoma (HeLa), hepato-carcinoma (PLC/PRF5, HepG2, Hep3B, and SK-HEP-1), colon (HCT116), lung (NCI-H460), breast cancer (MDA-MB231), and ovarian cancer (SKOV3) cell lines by reducing proliferation and inducing apoptosis, necrosis and autophagy (Lee et al, 2015). Aqueous extract of MWL and Anoplophora chinensis showed antiinflammatory activity against the colorectal adenocarcinoma cell line, Caco-2, and human hepatocellular carcinoma cell line, HepG2, and induced apoptosis by upregulating death receptor and caspase 3 expression (Ding et al, 2021).…”
Section: Insect Extractsmentioning
confidence: 99%
“…As mentioned above, it is believed that MTB possess many benefits for human health including the prevention of cardiovascular diseases, iron deficiency anemia, among others (Zhang, 2013). Previous studies have shown that MWL extracts possess antiproliferative effects against hepatocellular carcinoma cells (Lee et al., 2015). However, the effect of such extracts on other cancer cell lines has not yet been studied.…”
Section: Introductionmentioning
confidence: 98%